Tibial Tubercle Osteotomy in Total Knee Arthroplasty: Midterm Results Experience of a Monocentric Study - Biggi, Stefano; Divano, Stefano; Tedino, Riccardo; Capuzzo, Andrea; Tornago, Stefano; Camera, Andrea (Joints, 2018)
Purpose Difficult primary total knee arthroplasty (TKA) and revision TKA may be high demanding, especially during joint exposure. Aim of this article is to evaluate the clinical and radiological outcomes of a series of patients, who underwent TKA and revision TKA, where tibial tubercle osteotomy (TTO) was performed.Methods We retrospectively reviewed a cohort of 79 consecutives TKAs where TTO was performed. Patients were assessed clinically and radiographically at their last follow-up (mean, 7.4 ± 3.7 years). Clinical evaluation included the Knee Society Score (KSS), the pain visual analogue scale (VAS), and range of motion. Radiological assessment included the evaluation of radiolucent lines, osteolysis, cortical bone hypertrophy, time of bone healing of the TTO fragment, and the hardware complication.Results KSS raised from 40.7 ± 3.1 to 75 ± 4.3 (p < 0.0001). Knee flexion increased from 78.7 ± 9.9° to 95.0 ± 9.5° (p < 0.0001), and VAS improved from 7.9 ± 0.9 to 3.8 ± 1 (p < 0.0001). No signs of loosening or evolutive radiolucency lines were found. Osteolytic areas around the stem were detected. No significant association was found between the implant design and the outcomes, while aseptic loosening showed significantly better results. Complications were: 4 painful hardware, 3 late periprosthetic infections, 1 extension lag of 5°, and 3 flexion lag.Conclusion Our experience suggests the use of TTO to improve the surgical approach in difficult primary TKA or revision TKA. A precise surgical technique leads to good results with low risk of complications.Level of Evidence Level IV, therapeutic case series.
Keywords: tibial tubercle osteotomy; total knee arthroplasty; revision; surgical approach